Detection of Plant Pathogens and Their management - Jeevan P verma; Anupam varma (New Delhi Angkor, 1995)
this book dscribed the progress of disease depends on five of its main components, namly, the pathogen, the host, the the environment, the element of time and the activities of humans.
Glasshouse Laboratory Enterobacter
Keywords: Glasshouse, Laboratory, Enterobacter